Impact of SAfinamide on Depressive Symptoms in Parkinson’s Disease Patients (SADness-PD Study): A Multicenter Retrospective Study - Peña, Esteban (Brain Sci, 2021)
Background: We aimed to assess the effects of safinamide on depression, motor symptoms, and the serotonin syndrome related to its co-administration with antidepressants in patients with Parkinson’s disease (PD). Methods: We retrospectively analyzed the data of patients at 1 and 3 months of follow-up compared to baseline. Results: n = 82 (safinamide 50 mg = 22, 100 mg = 60, with antidepressants = 44). First, we found improvement in depression (Hamilton Depression Rating Scale: −6 ± 5.10 at 1 month and −7.27 ± 5.10 at 3 months, p < 0.0001; Patient Global Impression of Improvement Scale: 60.3% and 69.5% of patients at 1 and 3 months reported some improvement). Second, safinamide improved the daily life activities and motor symptoms/motor complications (Unified Parkinson’s Disease Rating Scale (UPDRS-II): −2.51 ± 6.30 and −2.47 ± 6.11 at 1 and 3 months, p < 0.0001; III: −3.58 ± 8.68 and −4.03 ± 8.95 at 1 and 3 months, p < 0.0001; IV: −0.61 ± 2.61 and −0.8 ± 2.53 at 1 and 3 months, p < 0.0001). Third, 7.31% and 8.53% of patients developed non-severe adverse events related to safinamide at 1 and 3 months. Serotonin syndrome was not observed in the patients treated with antidepressants; some isolated serotonin syndrome symptoms were reported. Conclusions: Safinamide could be useful for treating depression in PD; it was effective for motor symptoms and motor complications and safe even when co-administered with antidepressants.